Algerian gas in transition: domestic transformation and changing gas export potential - Ouki, M (Oxford Institute for Energy Studies, 2019)
Algeria is at a critical stage in its history. Since February 2019, people of all strata have been taking to the street to press for radical political changes. This will undoubtedly have far-reaching implications for the country’s future and its economy. An economy that has long been driven by the hydrocarbon sector and where oil and gas exports still account for over 95 per cent of total export revenue. Algeria’s hydrocarbon endowment is dominated by its larger natural gas reserves compared to crude oil. The country, which has been producing, consuming and exporting natural gas for several decades, has reached a point where its gas balance is facing severe challenges. A declining or, at best, stagnating natural gas production and a rapid domestic gas consumption growth have combined to constrain dangerously the country’s gas export potential. The reduction of gas export revenue has led to some government energy policy responses, including a revised hydrocarbons law (yet-to-be issued) to relaunch upstream investments in partnership with international oil and gas companies. But, actions to address the issue of subsidized domestic electricity and gas prices remain absent. There is hope, though, that this state of affairs that has lasted for decades at a very high financial cost could be addressed gradually. The reasons for a potentially fundamental policy change are mainly the fact that the Algerian economy can no longer afford this heavy financial burden and the impact of the on-going political transformation.